Genomic Investigation to Identify Sources of Severe Acute Respiratory Syndrome Coronavirus 2 Infection Among Healthcare Personnel in an Acute Care Hospital. (31st October 2022) - Sansom, Sarah E; Barbian, Hannah; Hayden, Mary K; Fukuda, Christine; Moore, Nicholas M; Thotapalli, Lahari; Baied, Elias J; Kim, Do Young; Snitkin, Evan; Lin, Michael Y; ,
Abstract: Background: Identifying the source of healthcare personnel (HCP) coronavirus disease 2019 (COVID-19) is important to guide occupational safety efforts. We used a combined whole genome sequencing (WGS) and epidemiologic approach to investigate the source of HCP COVID-19 at a tertiary-care center early in the COVID-19 pandemic. Methods: Remnant nasopharyngeal swab samples from HCP and patients with polymerase chain reaction–proven COVID-19 from a period with complete sample retention (14 March 2020 to 10 April 2020) at Rush University Medical Center in Chicago, Illinois, underwent viral RNA extraction and WGS. Genomes with >90% coverage underwent cluster detection using a 2 single-nucleotide variant genetic distance cutoff. Genomic clusters were evaluated for epidemiologic linkages, with strong linkages defined by evidence of time/location overlap. Results: We analyzed 1031 sequences, identifying 49 clusters that included ≥1 HCP (265 patients, 115 HCP). Most HCP infections were not healthcare associated (88/115 [76.5%]). We did not identify any strong epidemiologic linkages for patient-to-HCP transmission. Thirteen HCP cases (11.3%) were attributed to a potential patient source (weak evidence involving nonclinical staff that lacked location data to prove or disprove contact with patients in same cluster). Fourteen HCP cases (12.2%) were attributed to HCP source (11 with strong evidence). Conclusions: Using genomic and epidemiologic data, we found that most HCP severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections were not healthcare associated. We did not find strong evidence of patient-to-HCP transmission of SARS-CoV-2. Abstract : Using a combined genomic and epidemiologic approach, we found that most healthcare personnel (HCP) SARS-CoV-2 infections were acquired from the community and from other sick HCP. We did not find strong evidence to support patient-to-HCP infection.